Assurdo della Storia, assurdo dell’opera. Modo e voce in Contro-passato prossimo - Blasi, Lorenzo (L'ospite ingrato, 2025)
This essay examines Guido Morselli’s Contro-passato prossimo (1975) within the framework of uchronia. It analyzes the tension between the nineteenth-century narrative surface and the strategies of discourse, centered on the omniscient narrator, using rhetorical and narratological tools. It also interprets the role of metalepsis at the core of the novel, highlighting the influence of Giuseppe Rensi’s philosophy on Morselli’s thought.